Spreading Hoax Information During The Covid-19 Pandemic - Sabit Sabit; Seli Nursafitri (The International Journal of Politics and Sociology Research, 2021)
The development of information technology today is very modern so that anyone can see information anywhere, especially nowadays almost everyone has a gadget and television so that information can be viewed and accessed anywhere, which in the end many people spread hoax news about the current situation. namely the COVID-19 pandemic which finally everyone was affected by the hoax news, moreover the current covid-19 virus is troubling everyone so that they are afraid especially with the emergence of hoax news that is not true. With current technological developments, hoax news information easily occurs through the media social media, namely on Facebook, YouTube, Instagram and other apks. The theory used in this study is the theory put forward by McLuhan. Medium is the message, where the medium For McLuhan, the media is a change in innovation or the discovery of new ideas while messages or message is the effect of these changes. The method in this study uses qualitative research methods, case studies of hoax news spread on Facebook social media accounts and data collection with social media is done by filling out questionnaires distributed to the Sagalaherang Subang community who have a Facebook account and are actively used using the Google Forms application. The results of this study indicate that the Subang Sahalaherang community understands the hoax news that is shared and does not immediately believe it and their attitude is indifferent to the hoax news circulating in Sagalaherang.